ANALISIS PENGULANGAN KATA YANG DIGUNAKAN OLEH PRE-SERVICE TEACHER PROGRAM STUDI BAHASA INGGRIS UNIVERSITAS RIAU - Jismulatif Jismulatif; Elvi Haprianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Repetition is a learning strategy that teachers have known many times and still use as it helps them teach the learning process in the classroom. This study investigated how student teachers use repetition in their first teaching practice experience. The researcher tried to find out the class of words that are most repeated by student teachers and also determined the function of repetition spoken by them in EFL classes. The data of this study came from the teaching practice videos from student teachers of English study program, Universitas Riau. This research used the framework Pragmatic analysis to analyze the function of repetition. From the study result, there were 144 repetitions spoken by six student teachers during teaching practice. It was found that repetition used by the teacher functions as a confirmation, giving information, repairing/correction, as emphasis, eliciting specific information, gathering students' attention, asking for information, and giving clear instructions to the students.